To Calculate Perception: Mathematical Analysis of Performance Art’s Press (Itinera, 2019)
The article focuses on the results of a sociological method of Content Analysis of texts concerning performance art with the aim of tracking a kind of objective history of artistic “performance” in France from the 1970s to the present time. In regards to the issue of theatre policy, this research reveals the effects produced by the press, intended as a political mechanism, on the development of artistic performance.